Children’s Gender Worldviews: Exploring Gender, Diversity, and Participation Through Postmodern Picture Books - Carolina Gonçalves; Catarina Tomás; Aline Almeida (Education Sciences)
Postmodern picture books offer valuable opportunities for children to engage with multiple perspectives and develop critical thinking skills. When used in pedagogical practices that prioritize children’s rights, agency, and voices, these books can effectively challenge dominant social norms and promote justice and equity. Within the framework of the SMOOTH project (Educational Common Spaces, Passing through Enclosures and Reversing Inequalities, Horizon 2020, EU), this qualitative study explores how children aged six to eight attending a public primary school in Lisbon, Portugal, make sense of gender through postmodern picture books. Grounded in the Educational Studies and Sociology of Childhood, the research analyses children’s understandings of gender and the meanings they construct concerning it. A six-month intervention program, consisting of read-aloud sessions, was conducted with children from diverse linguistic and socioeconomic backgrounds. Data were collected through focus groups and observation. Qualitative content analysis highlights how picture books can stimulate critical discussions on the social construction of gender, providing children with opportunities to reflect on differences, power relations, and social change. These findings indicate that embedding a care perspective further strengthens the recognition of children’s lived experiences and enriches educational practices by fostering inclusiveness and deeper understanding.